DTWGs are reviving Cambodia’s floodplain ecosystems - Sok, Sao; De Silva, Sanjiv (CGIAR System Organization, 2025)
Cambodia’s diverse natural ecosystems remain central to meeting national development goals. Yet, natural resources management (NRM) is complex, with conflicts over access between uses and users inhibiting more sustainable and equitable development. Water is illustrative, exemplified by the tug-of-war between freshwater ecosystems and rice production in Cambodia’s Tonle Sap Lake’s (TSL) floodplain. This threatens the diversity, productivity, and resilience of aquatic ecosystems, associated food production, and the livelihoods of hundreds of thousands of households. Despite Cambodia’s decentralized governance structure, the water, fisheries, agriculture and environment sectors exhibit limited cooperation, despite the fact the multi-functionality of water demands collaborative management. Although Cambodia’s development policies call for more cooperation, an innovative institutional model was needed to operationalize this by bringing diverse actors together to resolve local NRM issues.